HDAC6 Facilitates PRV and VSV Infection by Inhibiting Type I Interferon Production - Hu Zheng; Xiaohui Yang; Haiwen Zhong; Changxu Song; Zhenfang Wu; Huaqiang Yang (Viruses)
HDAC6 modulates viral infection through diverse mechanisms. Here, we investigated the role of HDAC6 in influencing viral infection in pig cells with the aim of exploiting the potential antiviral gene targets in pigs. Using gene knockout and overexpression strategies, we found that HDAC6 knockout greatly reduced PRV and VSV infectivity, whereas HDAC6 overexpression increased their infectivity in PK15 cells. Mechanistic studies identified HDAC6 as a DNA damage inhibitor in PK15 cells. HDAC6 overexpression attenuated DNA damage levels, which can further reduce type I IFN production to promote viral infection. Conversely, HDAC6 deficiency can limit viral infection by increasing DNA damage-mediated type I IFN production. This work demonstrates that HDAC6 affects the infection process of multiple viruses by modulating type I IFN production, highlighting a regulatory role of HDAC6 linking host immune response and viral infection levels in pig cells.